2018
DOI: 10.1101/399600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The association between adiposity and inpatient hospital costs in the UK Biobank cohort

Abstract: BackgroundHigh adiposity is associated with higher risks for a variety of adverse health outcomes, including higher rates of age-adjusted mortality and increased morbidity. This has important implications for the management of healthcare systems, since the endocrinal, cardiometabolic and other changes associated with increased adiposity may be associated with substantial healthcare costs. MethodsWe studied the association between various measures of adiposity and inpatient hospital costs through record linkage… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…These associations between BMI and annual costs are broadly consistent with other large and high-quality studies from the UK and elsewhere (8,(11)(12)(13)22). Based on the same cohort, Dixon et al (13) reported that a 2-kg/m 2 higher BMI was associated with an approximately 5.9% higher cost across the entire BMI range.…”
Section: Comparison With Other Studiessupporting
confidence: 79%
See 2 more Smart Citations
“…These associations between BMI and annual costs are broadly consistent with other large and high-quality studies from the UK and elsewhere (8,(11)(12)(13)22). Based on the same cohort, Dixon et al (13) reported that a 2-kg/m 2 higher BMI was associated with an approximately 5.9% higher cost across the entire BMI range.…”
Section: Comparison With Other Studiessupporting
confidence: 79%
“…These associations between BMI and annual costs are broadly consistent with other large and high-quality studies from the UK and elsewhere (8,(11)(12)(13)22). Based on the same cohort, Dixon et al (13) reported that a 2-kg/m 2 higher BMI was associated with an approximately 5.9% higher cost across the entire BMI range. Similarly, using data on over 1 million women aged 55 to 79 years in England, Kent et al (12) reported that every additional 2 kg/m 2 above 20 kg/m 2 was associated with 7.7% higher costs, which compares with 8.4% higher costs in the present study.…”
Section: Comparison With Other Studiessupporting
confidence: 79%
See 1 more Smart Citation
“…CCG was included as a random effect, and robust standard errors used to allow for potential misspecification of the link and family function. 23,24 Marginal effects were calculated and represent a change in the outcome for an increase in the exposure, keeping all other covariates at their observed levels, and averaged over all patients. Models were adjusted for demographic, clinical, and practice factors, and non-linear associations for all continuous measures were investigated.…”
Section: Doac Uptake Adverse Events and Economic Outcomes (2012 To mentioning
confidence: 99%
“…A patient undergoing an inpatient hospital visit will occupy a bed but does not necessarily stay overnight. The process by which episodes of care were coded to reflect costs are described elsewhere [55, 56]. Briefly, episodes of inpatient hospital care were coded to create hospital resource groups (HRGs), which denote episodes of care with similar diagnoses, operations and procedures.…”
Section: Datamentioning
confidence: 99%